2021
DOI: 10.1016/j.isci.2021.103245
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of neural network dysfunction and microglial alterations in Alzheimer’s disease-related models

Abstract: Summary Nonconvulsive epileptiform activity and microglial alterations have been detected in people with Alzheimer’s disease (AD) and related mouse models. However, the relationship between these abnormalities remains to be elucidated. We suppressed epileptiform activity by treatment with the antiepileptic drug levetiracetam or by genetic ablation of tau and found that these interventions reversed or prevented aberrant microglial gene expression in brain tissues of aged human amyloid precursor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 92 publications
(183 reference statements)
2
11
0
Order By: Relevance
“…These data are consistent with recent work that showed that treatment with LEV in aged hAPP mice prevented aberrant microglia gene expression. 36 The authors suggest that epileptiform activity observed in this model influences microglia directly, and that the reduction of the microglial gene TREM2 exacerbates this activity. This is consistent with the known regulation of phagocytosis via TREM2‐activation of PLCG2, 20 , 21 which would result in impaired amyloid clearance in this model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These data are consistent with recent work that showed that treatment with LEV in aged hAPP mice prevented aberrant microglia gene expression. 36 The authors suggest that epileptiform activity observed in this model influences microglia directly, and that the reduction of the microglial gene TREM2 exacerbates this activity. This is consistent with the known regulation of phagocytosis via TREM2‐activation of PLCG2, 20 , 21 which would result in impaired amyloid clearance in this model.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the proposed mechanism of action of LEV as a neuromodulator of synaptic transmission, 1,7 these results were not surprising, and suggest that earlier treatment and longer duration with LEV may be required to accomplish this outcome, and are consistent with a number of preclinical studies that have used LEV in amyloid models. 14,16,36 Functional testing revealed dose-dependent increases in hyperactivity (Figure 4), which may be indicative of potential side effect profile of LEV. However, given the therapeutic index for the dose range based on PK/PD and in consideration of the allometric scaling data, the dose range for side effects relative to the efficacious dose range may not be a major concern.…”
Section: Discussionmentioning
confidence: 96%
“…Different groups looked at the effect of tau reduction on seizure susceptibility, with or without the presence of amyloid alterations and most found that tau reduction led to less‐severe seizures. 12 , 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…Different groups looked at the effect of tau reduction on seizure susceptibility, with or without the presence of amyloid alterations and most found that tau reduction led to less-severe seizures. 12,43,44 One report of a study of seizures in an AD model with both amyloid and tau mutations showed that 3xTg mice were more susceptible to audiogenic seizures at the age of 3 weeks. 13 Biomarker analysis was limited to IHC with the 6E10 antibody, which demonstrated the presence of Aβ or APP in HC neurons.…”
Section: F I G U R Ementioning
confidence: 99%
“…This neuroinflammatory panel reports the activity of 23 neuroinflammation pathways and processes across five brain cell types and 14 cell types of the peripheral immune system. We chose this approach since it is validated in Alzheimer’s models, highly sensitive, and measures mRNAs without cDNA amplification (Das et al, 2021; Ramesha et al, 2021). We performed NanoString quantification in wild type, SLC25A1Δ , and SLC25A4Δ HAP1 cells, as well as in iPSC-derived astrocytes treated for 48 hours with sublethal doses of antimycin (Fig.…”
Section: Resultsmentioning
confidence: 99%